Can We Achieve More with Less? Parenchymal Sparing Surgery Versus Major Liver Resection for Colorectal Liver Metastases: An Observational Single-Center Study with Propensity Score Analysis - Sorinel Lunca; Stefan Morarasu; Raluca Zaharia; Andreea-Antonina Ivanov; Cillian Clancy; Luke O’Brien; Wee Liam Ong; Gabriel-Mihail Dimofte (Diagnostics)
Background/Objectives: Colorectal liver metastases (CRLMs) occur in 25–30% of colorectal cancer (CRC) patients, significantly impacting survival. While major liver resection (MLR) was traditionally preferred for oncologic clearance, parenchymal-sparing surgery (PSS) has emerged as a less invasive alternative. This study compares perioperative and long-term outcomes of PSS versus MLR in CRLM patients. Methods: We conducted a retrospective cohort study at the Regional Oncology Institute, Iasi, Romania, analyzing patients who underwent hepatic resection for CRLM between August 2013 and June 2024. Patients were categorized into PSS (n = 58) and MLR (n = 28) groups. Outcomes assessed included perioperative parameters, postoperative morbidity, overall survival (OS), and disease-free survival (DFS). Results: PSS was associated with a shorter operative time (235.2 vs. 302.6 min, p = 0.003), lower morbidity (18.9% vs. 57.1%, p = 0.001), and fewer major complications (Clavien–Dindo ≥ III, p = 0.005). ICU stay was significantly longer in MLR patients (p = 0.04). After propensity score matching (PSM), PSS was found to have lower morbidity compared to MLR (p = 0.023) with similar major morbidity (p = 0.473) and LOS (p = 0.579). Overall survival (31 vs. 37.1 months, p = 0.884) and disease-free survival (25.2 vs. 22.2 months, p = 0.519) were comparable between the groups before and after propensity score matching PSM (40.9 vs. 21.2 months, p = 0.741 and 24.3 vs. 13.8 months, p = 0.653). Conclusions: PSS achieves comparable oncologic outcomes to MLR while reducing postoperative morbidity and ICU stay. These findings support PSS as the preferred approach for CRLM, reserving MLR for select cases requiring extensive resection.